At the Turn of the Nuclear Ages: Strategic Stability and Contours of a New World Order - V. A. Veselov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The year 2018 is rich with anniversaries. In the current international context the 50th anniversary of the Nuclear Non-Proliferation Treaty is certainly having special relevance. However, in the view of the need to examine the prospects of ensuring strategic stability, the role of nuclear weapons in world politics and the contours of the new world order yet another anniversary – twenty years from the beginning of the ‘second nuclear age’ – is just as important. In order to identify the substantive aspects of this phenomenon this paper provides a comparative analysis of distinctive features of both the first and the second nuclear ages. The author identifies the causes and prerequisites for the beginning of the ‘first nuclear age’ and examines, on the basis of a wide range of policy papers and analytical reports, the evolution of the United States’ approaches to nuclear strategy, deterrence and military and political goal setting. Special focus is on such issues as the achievement of strategic parity between the Soviet Union and the United States and the role of the Strategic Arms Limitation Talks Agreement and the 1972 Anti-Ballistic Missile Treaty in the development of the concept of strategic stability and informal code of conduct of nuclear powers. The paper emphasizes that although the ‘first nuclear age’ coincides chronologically with the Cold War, these two phenomena are not identical. As for the ‘second nuclear age’, the author links its emergence with such developments as India and Pakistan joining the nuclear ‘club’, long-range missile tests carried out by the DPRK, and the revision of the U.S. policy regarding the anti-missile defense which led to the abrogation of the Anti-Ballistic Missile Treaty. The author concludes that defining characteristics of the ‘second nuclear age’ include the retention of the ‘central deterrence’ accompanied by a growing importance of new political formats involving both nuclear and non-nuclear states, many of which have culturally specific approaches to military policy and strategic planning. All these factors combined form a backbone of military and political interactions between the leading powers within the emerging world order.